Optimization of Huang-Lian-Jie-Du-Decoction for Ischemic Stroke Treatment and Mechanistic Study by Metabolomic Profiling and Network Analysis - Zhang, Qian; Wang, Junsong; Liao, Shanting; Li, Pei; Xu, Dingqiao; Lv, Yan; Yang, Minghua; Kong, Lingyi (Frontiers in Pharmacology, 2017)
Introduction Stroke is one of the leading causes of death and adult disability worldwide, and ischemic stroke accounts for 87% of all forms of stroke patients (Lloyd-Jones et al., 2010; Strong et al., 2007). Unfortunately, no effective and generally accepted treatment for ischemic stroke is available now due to its complexity: multiple events occurred in ischemic stroke, such as excitotoxic amino acids, inflammation, oxidative damage, ionic imbalances, apoptosis, angiogenesis and neuroethology injury. Therefore, it is a huge challenge to rectify these abnormalities in clinic, especially with a single-target drug or monotherapy. Increasing evidences in treating complex illness such as ischemic stroke demonstrate that treatment regimens containing multiple drugs with distinct but related mechanisms can usually amplify the therapeutic efficacies of each agent, leading to maximal therapeutic efficacy with minimal adverse effects. Therefore, combination therapy has been a rational and promising choice (Amarenco 2006; Kernan et al., 2010). Actually, combination therapies have been advocated by prescriptions in the form of formulae in traditional Chinese medicine (TCM) for more than 2,500 years to prevent and cure diseases based on clinical practice (Wang et al., 2008). There is no doubt that, at least in some formulae, multiple components could hit multiple targets simultaneously and exert synergistic therapeutic efficacies. It is thus important to elucidate the complex action mechanism of TCM formulae to improve its clinical efficacy and safety, and for further drug or therapy development (Wang et al., 2008). Understanding optimal drug proportions and synergistic mechanisms of multicomponent drugs are critical for developing novel strategies to cope with complex diseases, such as stroke. The double complexity of ischemic stroke and the components of the formula created a far more difficult situation to assess the efficacy of the formula, needless to say, to clarify the combinatorial rules of herbal formula. Therefore, it’s urgent to employ new methods to elucidate the complex action mechanisms of TCM formulae, which is essential for further development of drugs or therapies based on these formulae. Metabolomics has been used as a versatile tool for the discovery of disease-related biomarkers and in assessment of the therapeutic effects of drug (Fan